Transgelin-2 in Multiple Myeloma: A New Marker of Renal Impairment? - Karolina Woziwodzka; Jolanta Małyszko; Ewa Koc-Żórawska; Marcin Żórawski; Paulina Dumnicka; Artur Jurczyszyn; Krzysztof Batko; Paulina Mazur; Małgorzata Banaszkiewicz; Marcin Krzanowski; Paulina Gołasa; Jacek A. Małyszko; et al. (Molecules, 2021)
Transgelin is a 22-kDa protein involved in cytoskeletal organization and expressed in smooth muscle tissue. According to animal studies, it is a potential mediator of kidney injury and fibrosis, and moreover, its role in tumorigenesis is emerging in a variety of cancers. The study included 126 ambulatory patients with multiple myeloma (MM). Serum transgelin-2 concentrations were measured by enzyme-linked immunoassay. We evaluated associations between baseline transgelin and kidney function (serum creatinine, estimated glomerular filtration rate—eGFR, urinary markers of tubular injury: cystatin-C, neutrophil gelatinase associated lipocalin—NGAL monomer, cell cycle arrest biomarkers IGFBP-7 and TIMP-2) and markers of MM burden. Baseline serum transgelin was also evaluated as a predictor of kidney function after a follow-up of 27 months from the start of the study. Significant correlations were detected between serum transgelin-2 and serum creatinine (R = 0.29; p = 0.001) and eGFR (R = −0.25; p = 0.007). Transgelin significantly correlated with serum free light chains lambda (R = 0.18; p = 0.047) and serum periostin (R = −0.22; p = 0.013), after exclusion of smoldering MM patients. Patients with decreasing eGFR had higher transgelin levels (median 106.6 versus 83.9 ng/mL), although the difference was marginally significant (p = 0.05). However, baseline transgelin positively correlated with serum creatinine after the follow-up period (R = 0.37; p < 0.001) and negatively correlated with eGFR after the follow-up period (R = −0.33; p < 0.001). Moreover, higher baseline serum transgelin (beta = −0.11 ± 0.05; p = 0.032) significantly predicted lower eGFR values after the follow-up period, irrespective of baseline eGFR and follow-up duration. Our study shows for the first time that elevated serum transgelin is negatively associated with glomerular filtration in MM and predicts a decline in renal function over long-term follow-up.